Biosorption of copper (CU) and lead (PB) by heavy metal resistant bacterial isolates from Iloilo River. - Ampuan, Naira Mitz W. (2012.)
Many indigenous organisms isolated from sites contaminated with heavy metals have tolerance to heavy metal toxicity and these microbial activities have always been the natural starting point for all biotechnological applications. It is therefore necessary to isolate bacterial strains with novel metabolic capabilities. In this study, a total number of 18 heavy metal-resistant bacteria (10 Pb-resistant and 8 Cu-resitant) were isolated from Iloilo River sediment samples (10degrees 41.974'N, 122degrees34.187' E). Bisorption of Cu and Pb by the bacterial isolates was characterized to evaluate their applicability for heavy metal removal from industrial waters. Selecting the highest resistance to metal toxicity and biosorption 4 isolates were identified by the phenotypic characterization. Identification of the top four metal-resitant isolates designates: Vibrio charchariae (83 percent) for Cu4; Vibrio harveyi (79 percent) for Cu6; Moraxella equi (100 percent) for Pb8; and Phoecoenobacter uteri (92 percent) for Pb9. Evaluation of specific metal biosorption by the isolates after incubation for 48h suggested that none of the isolates have good potential for bioremoval of metals from contaminated environments.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Copper -- Biosorption of -- Iloilo River; Lead -- Biosorption of -- Iloilo River; Heavy metal resistance -- Iloilo River